2018
DOI: 10.1111/dar.12830
|View full text |Cite
|
Sign up to set email alerts
|

Examining the factor structure of the Motives for Playing Drinking Games measure among Australian university students

Abstract: While the MPDG measure shows promise for assessing drinking game-specific motives, the need to consider the applicability of MPDG subscales across different samples was apparent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
4
9
0
Order By: Relevance
“…Results indicated that participants who played DGs frequently or consumed more drinks while playing also reported greater DG harms. The direction (Borsari et al, 2014; George et al, 2018; Johnson & Sheets, 2004) and strength (George et al, 2018) of these associations are consistent with other studies conducted with university students in the U.S. and Australia. This modified B-YAACQ-DG offers a valuable tool for comparing DG consequences among men/women and college/noncollege-attending young adults.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Results indicated that participants who played DGs frequently or consumed more drinks while playing also reported greater DG harms. The direction (Borsari et al, 2014; George et al, 2018; Johnson & Sheets, 2004) and strength (George et al, 2018) of these associations are consistent with other studies conducted with university students in the U.S. and Australia. This modified B-YAACQ-DG offers a valuable tool for comparing DG consequences among men/women and college/noncollege-attending young adults.…”
Section: Discussionsupporting
confidence: 91%
“…Despite this, only a handful of studies have assessed negative outcomes that occurred as a result of playing DGs among college students in the U.S. (e.g., Borsari et al, 2014; Diulio et al, 2014; Johnson & Stahl, 2004; Ray et al, 2014) and abroad (George & Zamboanga, 2018; George, Zamboanga, Martin, & Olthuis, 2018). For example, Johnson and Sheets (2004) assessed DG consequences and found that on average, men experienced more negative outcomes from playing DGs than women.…”
Section: Gendermentioning
confidence: 99%
“…Finally, coping-related drinking motives were negatively associated with the likelihood of playing DGs in-person. This finding aligns with studies conducted with U.S. ( Zamboanga et al, 2019 ) and Australian university students ( George et al, 2018 ) in which coping did not emerge as a motive to play DGs. We also observed a small but statistically significant association between COVID-related fears and coping motives in the current sample ( Table 1 ).…”
Section: Discussionsupporting
confidence: 89%
“…We acknowledge that this review does not provide insight into the differential association of motives with the problematic use of specific types of smartphone content (e.g., social networking, gaming). Consistent with substance use (Bachrach et al, 2012;George et al, 2018), it has been proposed that certain motives are likely unique to the problematic engagement in specific types of content accessible via a smartphone (Brand et al, 2019;Brand et al, 2016;Panova & Carbonell, 2018). However, as has been seen in the substance use literature (Cooper, 1994;Cooper et al, 2015;Kuntsche et al, 2005), there is also likely to be a set of core motives underlying generalised PSU, although there is yet to be consensus on precisely which motives.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%